L’abate e la nobildonna - Palmiero, Oreste (Quaderni Veneti, 2018)
The entire correspondence between Giacomo Zanella, poet and university professor from Vicenza, and Emilia Peruzzi Toscanelli, an active and dynamic figure of reference for culture and politics, mistress of one of the most sought-after nineteenth-century salons, will not fail to offer the reader different points of interest. Against the background of the cultural, political and historical events in a country, Italy, recovering from the post-unitarian wounds and often the subject of discussion between the two correspondents, the figures of the young Edmondo De Amicis and Renato Fucini, who at that time moved their first literary passages, also emerge.